2022
DOI: 10.1182/bloodadvances.2021005291
|View full text |Cite
|
Sign up to set email alerts
|

High risk of relapsed disease in patients with NK/T-cell chronic active Epstein-Barr virus disease outside of Asia

Abstract: Chronic active Epstein-Barr virus (EBV) disease (CAEBV) is characterized by high levels of EBV predominantly in T and/or NK cells with lymphoproliferation, organ failure due to infiltration of tissues with virus-infected cells, hemophagocytic lymphohistiocytosis (HLH) and/or lymphoma. The disease is more common in Asia than in the United States and Europe. While allogeneic hematopoietic stem cell transplantation (HSCT) is considered the only curative therapy for CAEBV, its efficacy and the best treatment modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…CAEBV is a systemic T‐ or NK‐cell lymphoproliferative disorder of immunosuppressed patients and it is defined by the presence of mononucleosis‐like symptoms for more than 3 months, high levels of EBV DNA in peripheral blood, as well as histological and RNA EBV tissue involvement 49,50 . It is a rare disorder, affecting children, and young adults more commonly, and there is no sex predilection.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…CAEBV is a systemic T‐ or NK‐cell lymphoproliferative disorder of immunosuppressed patients and it is defined by the presence of mononucleosis‐like symptoms for more than 3 months, high levels of EBV DNA in peripheral blood, as well as histological and RNA EBV tissue involvement 49,50 . It is a rare disorder, affecting children, and young adults more commonly, and there is no sex predilection.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…CAEBV is a rare but life-threatening EBV-positive lymphoproliferative disease characterized by high levels of EBV in the blood and tissues and organ infiltration of EBV-infected T- and NK cells. [1,2,5] Currently, the diagnosis of CAEBV should meet the following criteria: IM-like symptoms persisting for >3 months, increased EBV-DNA in the peripheral blood, demonstration of EBV-RNA or viral proteins in affected tissues, and no evidence of immunodeficiency. [1] Most patients with CAEBV have systemic presentations such as fever, hepatosplenomegaly, lymphadenopathy, cytopenia, and skin rash.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis is associated with EBV-DNA viral loads, platelet levels, and age at onset. [5,6] At present, treatment options for patients with CAEBV are limited. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only way to cure CAEBV; however, severe complications due to EBV infection, lack of appropriate donors, and disease relapse after transplantation remain challenging.…”
Section: Introductionmentioning
confidence: 99%
“…35 Despite HSCT showing improved survival in several studies, Saldana et al found that 20 of 44 patients who underwent HSCT outside of Asia died at 52 months with most due to relapsed disease. 5,37 In conclusion, CAEBV is an important diagnostic consideration in patients presenting with recurrent or persistent IM-like symptoms.…”
Section: Caebvcaebv Of T-and Nk-cell Is Most Frequent In Patients Frommentioning
confidence: 98%